Synthesis, characterization and catalytic activity of novel Co(II) and Pd(II)-perfluoroalkylphthalocyanine in fluorous biphasic system; benzyl alcohol oxidation - ÖZER, METİN (WILEY, 2009)
Tetra kis[heptadecafluorononyl] substituted phthalocyanine complexes were prepared by template synthesis from 4-(heptadecafluorononyloxy)phthalonitrile with Co(CH3COO)(2)center dot 4H(2)O or PdCl2 in 2-N,N-dimethylaminoethanol. The corresponding phthalonitrile was obtained from heptadecafluorononan-1-ol and 4-nitrophthalonitrile with K2CO3 in DMF at 50 degrees C. The structures of the compounds were characterized by elemental analysis, FTIR, UV-vis and MALDI-TOF MS spectroscopic methods. Metallophthalocyanines are soluble in fluoroalkanes such as perfluoromethylcyclohexane (PFMCH). The complexes were tested as catalysts for benzyl alcohol oxidation with tert-butylhydroperoxide (TBHP) in an organic-fluorous biphasic system (n-hexane-PFMCH).The oxidation of benzyl alcohol was also tested with different oxidants, such as hydrogen peroxide, m-chloroperoxybenzoic acid, molecular oxygen and oxone in n-hexane-PFMCH. TBHP was found to be the best oxidant for benzyl alcohol oxidation since higher conversion and selectivity were observed when this oxidant was used. Copyright (c) 2008 John Wiley & Sons, Ltd.
Keywords: biphasic catalysis; oxidation; phthalocyanine; SUBSTITUTED PHTHALOCYANINES; COPPER PHTHALOCYANINES; ELECTRONIC-STRUCTURE; AEROBIC OXIDATION; DIOXYGEN; CYCLOHEXANE; EPOXIDATION; COMPLEXES; IRON(III); EFFICIENT